Settling characteristics of alumina nanoparticles in ethanol-water mixtures - Ilyas, S.U. (2013)
Nanofluids are considered as promising heat transfer fluids due to enhanced heat transfer ability as compared to the base fluid alone. Knowledge of settling characteristics of nanofluids has great importance towards stability of nanosuspensions. Sedimentation behavior of Alumina nanoparticles due to gravity has been investigated using different proportions of ethanol-water binary mixtures. Nanoparticles of 40 nm and 50 nm are used in this investigation at 23Â°C. Sediment height with respect to time is measured by visualization method in batch sedimentation. The effect of sonication on the sedimentation behavior is also studied using ultrasonic agitator. The effect of particle diameter, nanoparticle concentration and ethanol-water proportion on sedimentation behavior of nanofluids has been investigated and discussed. Â© (2013) Trans Tech Publications, Switzerland.